Manajemen Dana Infaq Produktif pada Program Tani Nusantara dalam Meningkatkan Perekonomian Para Petani di LAZNAS lembaga manajemen infaq (LMI) Kota Pasuruan - Ma'rifah, Anisatul; Fauziah, Nur Dinah; Sundari (Al-Musthofa: Journal of Sharia Economics, 2021)
Infak means spending a portion of assets or income or income for an interest ordered by Islam. In order to manage infaq funds, a special and official institution is needed in order to achieve the objectives of infaq. One of them is LAZNAS Infaq Management Institute (LMI) Pasuruan City in the Nusantara Farmer program. The Nusantara Farmer Program is LMI's follow-up program in the economic field targeting dhuafa' farmers in the Pasuruan area who lack capital in cultivating their paddy fields. In order for the program to be implemented properly, management functions are needed which include: planning, organizing, actuating, and controlling. The purpose of this research is to find out how the management of productive infaq funds is carried out by LMI Pasuruan City in this Nusantara Farmer program. The type of research used is descriptive qualitative using field research methods with research sites at LAZNAS Infaq Management Institute (LMI) Pasuruan City which is located at Perum Puri Candi Blok BC No. 42 Purworejo, Pasuruan. This research was conducted by going into the field to obtain data through observation and interviews with staff, facilitators, and farmers assisted by the Nusantara Farmer program at LMI, Pasuruan City. The results obtained after conducting field research are that the management of productive infaq funds in the Nusantara Farmer program at LAZNAS LMI Pasuruan City has been running well and according to procedures. However, supervision is still not optimal, especially in terms of reporting harvest results, with routine reporting results can show the extent to which the Tani Nusantara program is developing. The role of productive infaq funds is quite large in improving the farmers' economy. As the researchers found, after participating in the Nusantara Farmer program from LAZNAS LMI, Pasuruan City, the assisted farmers experienced several changes in income levels, knowledge, and the economy towards a better standard of living. Besides that, it is able to encourage the Assisted Farmers to issue agricultural zakat when it reaches the nishab. Keywords: Management, Productive Infaq, Nusantara Farmers, Economic Improvement